2016
DOI: 10.1038/srep37094
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Focused-Ultrasound Mediated Drug Delivery to the Heterogeneous Primate Brain In Vivo with Acoustic Monitoring

Abstract: Focused ultrasound with microbubbles has been used to noninvasively and selectively deliver pharmacological agents across the blood-brain barrier (BBB) for treating brain diseases. Acoustic cavitation monitoring could serve as an on-line tool to assess and control the treatment. While it demonstrated a strong correlation in small animals, its translation to primates remains in question due to the anatomically different and highly heterogeneous brain structures with gray and white matteras well as dense vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 59 publications
1
48
1
Order By: Relevance
“…inter-animal variation, physiological condition) dynamics of the experiment. The major advantage of the proposed method is that it enables to characterize different level of activities with corresponding 'activity bands' for an individual animal and for the given experimental In previous studies, the correlation between spectral components of the MB emission and FUS induced BBB opening have been reported in different animal models (Wu et al, 2016;Vykhodtseva et al, 1995). It has been shown that harmonic, sub-harmonic, ultra-harmonic activity and broad-band noise can serve as indicators to measure the cavitation level and therefore to monitor BBB opening (McDannold et al, 2006;Tung et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…inter-animal variation, physiological condition) dynamics of the experiment. The major advantage of the proposed method is that it enables to characterize different level of activities with corresponding 'activity bands' for an individual animal and for the given experimental In previous studies, the correlation between spectral components of the MB emission and FUS induced BBB opening have been reported in different animal models (Wu et al, 2016;Vykhodtseva et al, 1995). It has been shown that harmonic, sub-harmonic, ultra-harmonic activity and broad-band noise can serve as indicators to measure the cavitation level and therefore to monitor BBB opening (McDannold et al, 2006;Tung et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Passive cavitation detection (PCD) was proposed for real-time transcranial monitoring of the bubble behavior and resulting cavitation activity during FUS sonication (McDannold et al, 2006). Recently, PCD-based cavitation metrics have been utilized to predict the cavitation dose and BBB opening size (Tung et al, 2011), delivery efficiency of the molecules (Wu et al, 2016) and permeability and reversibility of BBB opening (Sun et al, 2015). It has been shown that FUS induced BBB opening does not necessarily require the occurrence of inertial cavitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies using NHP has been reported that have yielded essential information on the safety of repeated sonication sessions 26,27 was demonstrated, as well as the influence of anesthesia in the BBB opening volume 28 and the associated drug delivery efficiency regarding the heterogeneity of brain anatomy and vasculature. 29 Current FUS systems employed for BBB disruption in NHP's and humans adopted low-frequency ranges (220 kHz 26 or 500 kHz 30 ) or implantable devices 31,32 to overcome the skull effects. A clinical system primarily designed for thermal ablation of the brain has been used in NHPs with the advantage of also providing MRI guidance 33 -so-called magnetic resonance imaging-guided focused ultrasound (MRgFUS).…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, Nakagami imaging, heating‐induced echo strain and speckle tracking, backscatter energy monitoring, tissue stiffness and elastographic methods, phase aberration contrast analysis, speed of sound (SOS) mapping, acoustic emission, acoustic harmonic monitoring, attenuation mapping, and statistical methods, among others. In addition, nonthermal methods that monitor the cavitation activity have been useful in acoustically monitoring blood‐brain barrier disruption and drug delivery doses as well …”
mentioning
confidence: 99%